1994
DOI: 10.1021/ma00100a050
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Network Formation by Photopolymerization of Liquid Crystal Monomers in a Low Magnetic Field

Abstract: Liquid crystalline mixtures of mono-and dimethacrylates were photopolymerized after macroscopic orientation of the monomers under a relatively weak magnetic field or via interaction with a unidirectionally rubbed polyimide substrate. Polymerization kinetics was followed by a thermoanalysis technique, and the transmitted light intensity was measured in real time. The macroscopic order parameter of one of the component comonomers (bearing a cyano group) incorporated into the polymer network prepared under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Experimental technique lines of the aromatic cores of molecules 1 and 2 are The 13 C NMR measurements were performed in a separated. The lines overlap if both cores have identical magnetic ® eld of 11´7 T at a frequency of 125 M Hz using chemical surround ings ( left hand phenyl rings in a Bruker M SL 500 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental technique lines of the aromatic cores of molecules 1 and 2 are The 13 C NMR measurements were performed in a separated. The lines overlap if both cores have identical magnetic ® eld of 11´7 T at a frequency of 125 M Hz using chemical surround ings ( left hand phenyl rings in a Bruker M SL 500 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Althoug h temperature shifts due to elastic director deformations the polymerized samples are now in a gel-lik e state, the are absent, althoug h the latter have been observed for ligh t scattering characteristics are similar to those of the liquid crystals which are con® ned to spheres in mixtures nematic phase. For the 13 C NMR measurements, the with high polymer concentration s or glasses [ 28 ]. W ith tube axis, which coincides with the alignmen t axis of increasing temperature, and above the transition point, the network, lies perpendicular to the applied magnetic the negative shifts of the nematic lines decrease slowly.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…This kind of optically anisotropic LCN can be used as an optical compensation film for a liquid-crystal display (LCD) to resolve its narrow-viewing-angle problem. [1][2][3][4] Recently, Broer and coworkers, [5][6][7][8][9][10][11][12][13][14] Hikmet and coworkers, [15][16][17][18][19][20] and Hoyle et al 21 demonstrated that macroscopically oriented LCNs can be obtained by in situ photopolymerization of difunctional liquid-crystal monomers (LCMs) in contact with unidirectionally rubbed thin-film substrates. During polymerization, the ordering of the mesogen was fixed, yielding a uniaxially crosslinked network.…”
Section: Introductionmentioning
confidence: 99%